Evaluation of the association between bevacizumab concentration and clinical outcomes in patients with breast cancer brain metastasis - Chih-Ning Cheng; Yun-Jung Tsai; Huai-Hsuan Chiu; Tom Wei-Wu Chen; Ching-Hung Lin; Yen-Sheng Lu; Ching-Hua Kuo (Heliyon)
Bevacizumab is widely used in various clinical indications, but investigations into its optimal dosage for treating CNS metastases remain limited. The BEEP regimen, comprising bevacizumab, etoposide, and cisplatin, has recently demonstrated promising clinical outcomes for patients with breast cancer brain metastasis (BCBM) or leptomeningeal metastasis (LM). This study aimed to evaluate the exposure-response relationship of bevacizumab in BCBM patients and to explore the improved CNS penetration of chemotherapy by bevacizumab with LM patients. Twenty-two BCBM patients and six LM patients receiving the BEEP regimen were enrolled. For BCBM patients, blood samples were drawn at trough level of cycles 1 and 6 to investigate the association between bevacizumab concentrations and clinical outcomes. For LM patients, plasma and cerebrospinal fluid (CSF) concentrations of bevacizumab and etoposide were measured to investigate the enhancement of etoposide penetration provided by bevacizumab. Concentration evaluation revealed that bevacizumab plasma concentrations substantially varied between individuals. Additionally, concentrations increased after 6 cycles, indicating bevacizumab accumulation during treatment. Although bevacizumab concentrations did not associate with therapeutic response and progression-free survival, patients with higher bevacizumab concentrations exhibited longer overall survival (adjusted HR 0.78; p = 0.039). Furthermore, a positive correlation was observed between time-weighted average concentration of plasma bevacizumab and CSF penetration of etoposide on day 2 (post-bevacizumab) relative to day 1 (pre-bevacizumab) (r = 0.83; p = 0.042). These findings offer valuable insights into the application of therapeutic drug monitoring of bevacizumab to improve survival outcomes in BCBM patients. Further studies are warranted to determine the optimal bevacizumab concentration.